2011
DOI: 10.5205/reuol.1262-12560-1-le.0507201119
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a group of nurses on the process of caring for patients with permanent colostomy

Abstract: Objective: to understand the perceptions of a group of nurses on the process of taking care for patients with permanent colostomy. Methodology: it’s a qualitative research focused on phenomenology. It was carried out by eight nurses from the Specialized Course in Family Health, Institute of Continuing Education PUC Minas. This project was approved by the Ethics Committee of the Pontifical Catholic University of Minas Gerais, paragraph number CAAE: 0101.0.213.000-10. The data collection was done through recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…12 Thus, the category "Feelings about the stoma before and after ostomy surgery" demonstrated that, without an alternative before surgery, the candidate was left with the only option of accepting it, although it represented the difference between life and death. The lack of experience with a stoma can lead to an emotional breakdown after surgery, causing the people with a stoma to often make references to death.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, the category "Feelings about the stoma before and after ostomy surgery" demonstrated that, without an alternative before surgery, the candidate was left with the only option of accepting it, although it represented the difference between life and death. The lack of experience with a stoma can lead to an emotional breakdown after surgery, causing the people with a stoma to often make references to death.…”
Section: Discussionmentioning
confidence: 99%
“…Pessoa ostomizada ou estomizada é aquela que passou pelo procedimento cirúrgico no qual se realiza a exteriorização de parte de um órgão oco, como o intestino ou a bexiga, criando uma abertura no abdômen chamada de estoma (1) . Trata-se de uma intervenção agressiva capaz de provocar várias mudanças na fisiologia corporal, no estilo de vida, no aspecto físico e psicossocial da pessoa (2) . sensuais, situação que influencia negativamente na vivência da sexualidade (3) .…”
Section: Introductionunclassified